2021
DOI: 10.1088/1742-6596/1811/1/012074
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Hierarchical Clustering Method in Analyzing Genetic Relationship on DNA SARS-CoV-2 Sequences

Abstract: In mid-September of 2020, WHO released data starting that more than 28 million people worldwide have contracted coronavirus. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the full name coronavirus, specifically Covid-19. This virus attacks the human respiratory system and can cause infection in the human lungs and even death. WHO noted that more than 900 thousand people worldwide have died due to being infected with the coronavirus. In Indonesia, more than 210 thousand people have been infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…where index i loops all the values in the vector. The Euclidean matrix distance is a measure of the geometric distance between two components based on the size (Matthiesen in [22]). The Euclidean distance is used to calculate each distance from each sequence after the 18dimensional MEV data is found.…”
Section: Distance Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…where index i loops all the values in the vector. The Euclidean matrix distance is a measure of the geometric distance between two components based on the size (Matthiesen in [22]). The Euclidean distance is used to calculate each distance from each sequence after the 18dimensional MEV data is found.…”
Section: Distance Matrixmentioning
confidence: 99%
“…The results of this study showed accurate and similar results when compared to other alignment methods using ClustalW, Clustal, MAFFT, and MUSCLE. A study by Banjarnahor et al [22] used hierarchical clustering and multiple sequence alignment (MSA) to analyze the SARS-CoV-2 DNA sequence. According to the findings of this study, the ancestors of SARS-CoV-2 originated in China.…”
Section: Introductionmentioning
confidence: 99%